Hubungan Tingkat Kepercayaan Diri dengan Keputusan Karir Studi Lanjut pada SMA Negeri 4 Denpasar 2026 - Mita Ayu Saputri; Made Wery Dartiningsih; I Wayan Juliawan (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study aims to examine the relationship between self-confidence and career decisions regarding higher education among 11th-grade students at SMA Negeri 4 Denpasar in 2026. A quantitative correlational research design was employed, involving 204 students selected through proportional random sampling. Data were collected using self-confidence and career decision questionnaires that had been tested for validity and reliability. The data were analyzed using the Pearson Product-Moment correlation test. The results revealed a positive and statistically significant relationship between self-confidence and career decisions for further study, with a correlation coefficient of r = 0.259 and a significance value of p = 0.000 (p < 0.05). These findings indicate that students with higher levels of self-confidence tend to make firmer and more confident decisions regarding their pursuit of higher education. Furthermore, the coefficient of determination showed that self-confidence contributed 67% to career decision-making, while the remaining 33% was influenced by other factors not examined in this study. Overall, the findings highlight the important role of self-confidence in supporting students’ readiness and certainty when determining their educational and career pathways. Therefore, guidance and counseling programs should focus on strengthening students’ self-confidence to facilitate more effective career planning and informed decisions about continuing their education.